Study of Some Biochemical Parameters in Epileptic Patients - E. Ibrahim , Dania; Kadhum H. Alhashemi, Wisam (Al-Nahrain Journal of Science, 2019)
Epilepsy is a worldwide disease characterized by huge changes in several biochemical parameters due to seizure the main symptoms of the disease. The aim of this study was to assess some biochemical parameters in epileptic patient. This study involves 31 patients with 31 healthy as a control group for each one of both groups, the following parameters were assessed: 8-hydroxydeoxy guanosine(8-OHdG), Malondialdehyde (MDA), Prolactin, Lactate dehydrogenase (LDH), Albumin, Total bilirubin (TSB), Alkaline phosphatase (ALP), Aspartate aminotransferase (AST), Alanine-aminotransferase (ALT) and Creatine phospho kinase (CPK) in serum of them. 8-OHdG concentration was increase significant (P> 0.05) in epileptic patients in compare to control group while MDA was nonsignificant, the seizure was characterized by increasing of oxidative stress situation according to its naturalistic effect mainly on nucleic acid (generate 8-OHdG) in cells more than lipid (generate MDA), due to generating oxidants inside the cell. TSB was significantly decreased (P> 0.05) may be due to its function as endogenous antioxidant. Albumin did not show any significant difference. CPK has significant increasing (P> 0.05) which be due to its seizure nature that need high energy production which stimulate the reactions of energy production which lead to upregulate that enzyme. LDH failed to show any significant difference may be due to fast remediation.